Laser heating of a finite silver sulfide slab (Ag2S). An elegant analytical solution using Laplace integral transform method. (JOURNAL OF ADVANCES IN PHYSICS, 2024)
The problem of heating a finite silver sulfide slab with cw laser is studied using Laplace integral transform technique. For a certain laser power irradiance an expression for the temperature profile within the slab is obtained. The temperature variations with time for the front and rear surfaces are also obtained. The critical time required to initiate melting can thus be computed. Computations for an illustrative example are given. The obtained results reveal.